Platform cooperativism: challenging the corporate sharing economy - Scholz, Trebor (New York, 2016)
"The “sharing economy” wasn’t supposed to be this way. Aided by the tiny computers most of us carry with us all day, every day, we would be free from the burdens of ownership and making money in our spare time by renting out our unused possessions. The vison was—or at least appeared to be—an idealistic one. Even before they enter kindergarten, every child learns the value of sharing, and here were the beneficent forces of Silicon Valley bringing us innovative new tools to strengthen our communities, disrupt outdated ways of doing business, and maybe even reduce our carbon footprints. The reality turned out to be a little different. Sure, Uber and its ilk offer remarkable convenience and a nearly magical user experience, but their innovation lies just as much in evading regulations as in developing new technology. Behind the apps lies an army of contract workers without the protections offered to ordinary employees, much less the backing of a union. This new economy is not really about sharing at all. Rather, as Trebor Scholz argues in this study, it is an on-demand service economy that is spreading market relations deeper into our lives. ..."